Quality Management System in Asphalt Pavement Toll Widening: Sistem Manajemen Mutu Perkerasan Aspal pada Pelebaran Tol Jakarta Cikampek - Nadia Laila Lathifah; Muhammad Isradi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Quality Management System (QMS) implementation is fundamental to ensuring construction quality in toll road infrastructure projects characterized by technical complexity and active traffic conditions. Specific Background: The Jakarta–Cikampek Toll Road lane widening project requires strict quality control in asphalt pavement works due to high traffic volume, environmental constraints, and operational risks. Knowledge Gap: Previous studies have predominantly addressed quality planning and ISO 9001 audits, while empirical evaluation of QMS implementation in asphalt pavement widening under live traffic conditions remains limited. Aims: This study aims to evaluate QMS implementation in asphalt pavement works and to develop a systematic and measurable Quality Key Performance Indicator matrix. Results: Using a quantitative survey of 70 project stakeholders analyzed through Importance Performance Analysis and SEM-PLS, the findings indicate that environmental and weather constraints as well as material quality fall into high-priority improvement areas, while managerial support shows the strongest positive relationship with implementation quality. Implementation quality significantly determines project performance, with R² values of 0.856 and 0.916 indicating strong predictive capability. Novelty: The integration of Importance Performance Analysis and SEM-PLS produces a practical KPI-based quality assessment instrument tailored to toll road widening projects. Implications: The proposed matrix provides a data-driven evaluation framework for prioritizing corrective actions, strengthening managerial commitment, and optimizing QMS application in asphalt pavement construction. Highlights• Environmental and weather constraints require urgent corrective prioritization in pavement works.• Managerial commitment demonstrates the strongest statistical relationship with execution standards.• Integrated analytical modeling produces a measurable KPI-based assessment framework. KeywordsQuality Management System; Asphalt Pavement; Importance Performance Analysis; SEM PLS; Toll Road Construction